Implementation of Intelligent Automated Gate System with QR Code - An IOT System to Help Gate Management - Hamid, E; Gee, LC; Bahaman, N; Anawar, S; Ayob, Z; Malek, AA (Science & Information Sai Organization Ltd, 2024)
This paper is about QR code-based automated gate system. The aim of the research is to develop and implement a type of medium-level security gate system especially for small companies that cannot afford to install high-tech auto gate system. IAGS is a system that uses valid staffs' QR code pass card to activate the gate without triggering the alarm. It is developed to connect to the internet and provide a real-time email notification if any unauthorized activities detected. Besides that, it is also designed to record all the incoming and outgoing activities for all staff. All QR code pass cards that are generated to staff will be encrypted to provide integrity to the data. The system is based on items such as PIR motion sensor, servo motor, Arduino microcontroller, Piezo buzzer, and camera. The software is implemented using VB. NET and the QR recognition level is about 99% accurate.